Analysis of Cyclin-Dependent Kinase 1 as an Independent Prognostic Factor for Gastric Cancer Based on Statistical Methods - Zhang, Xu; Ma, Hua; Zou, Quan; Wu, Jin (Frontiers in Cell and Developmental Biology, 2020)
Objective: To investigate the expression of Cyclin-dependent Kinase1 (CDK1) in gastric cancer (GC), evaluate its relationship with the clinicopathological features and prognosis of GC, and analyze the advantage of CDK1 as a potential independent prognostic factor for GC. Methods：TCGA data and corresponding clinical features of GC were collected. Firstly, the aim gene was selected by combining five topological analysis methods, where the gene expression in paracancerous and GC tissues was analyzed by Limma package and Wilcox test. Secondly, the correlation between gene expression and clinical features was analyzed by logistic regression. Finally, the survival analysis was carried out by using the Kaplan-Meier. The gene prognostic value was evaluated by univariate and multivariate Cox analysis, and the gene potential biological function was explored by GSEA enrichment analysis. Results: CDK1 was selected as one of the most important genes associated with GC. The expression level of CDK1 in GC tissues was significantly higher than that in paracancerous tissues, which was significantly correlated with pathological stage and grade. The survival rate of the CDK1 high expression group was significantly lower than that of the low expression group. CDK1 expression was significantly correlated with overall survival. CDK1 expression was mainly involved in prostate cancer, small cell lung cancer and gastric cancer and was enriched in WNT signaling pathway and T cell receptor signaling pathway. Conclusion: CDK1 may serve as an independent prognostic factor for GC. It is also expected to be a new target for molecular targeted therapy of GC.